Neuroinflammatory regulatory role of microglia in optic nerve injury: from pathological mechanisms to therapeutic targets - Gao, Miaoran; Zhou, Jian; Shi, Nannan; Yan, Xiaoling; Liang, Lina (Frontiers in Immunology, 2026)
Optic nerve injury, encompassing conditions such as glaucoma, optic neuritis, and traumatic optic neuropathy, is a major cause of irreversible vision loss. Traditional broad-spectrum anti-inflammatory treatments have shown limited efficacy, highlighting the need for precision-based therapeutic approaches grounded in the underlying pathological mechanisms. As the primary immune cells of the central nervous system (CNS), microglia play a crucial role in regulating neuroinflammation following optic nerve injury. This review provides a comprehensive overview of the mechanisms governing microglial neuroinflammatory regulation, including early inflammatory signal recognition mediated by damage-associated molecular patterns (DAMPs), dynamic transcriptional networks regulating polarization between pro-inflammatory and pro-repair phenotypes, bidirectional modulation of phagocytic clearance by the complement system, and the complex multicellular interactions among microglia, astrocytes, and Müller cells. The concept of conditioning injury conditioning injury (intraocular inflammatory stimulation) has revealed the dual nature of neuroinflammatory responses: through temporal polarization shifts, microglia can both release neurotoxic mediators that worsen injury and secrete neurotrophic factors that promote axonal regeneration and myelin repair. This shift from traditional broad-spectrum anti-inflammatory strategies to precision functional modulation forms the basis for emerging therapeutic approaches, including PPARγ pathway activation, selective complement system targeting, and time-dependent modulation. We also assess the potential of advanced technologies, such as nanodelivery systems, single-cell analysis, and molecular imaging, in precision diagnosis and treatment. Finally, we critically examine the limitations of current research, including interspecies variability, model constraints, and clinical translation barriers, and discuss the translational potential of microglia-targeted therapies in protecting and restoring clinically meaningful visual function.